Angiotensin II Promotes White Adipose Tissue Browning and Lipolysis in Mice. (27th June 2022) - Cai, Zhaohua; Fang, Liang; Jiang, Yangjing; Liang, Min; Wang, Jian; Shen, Yejiao; Wang, Zi; Liang, Feng; Huo, Huanhuan; Pan, Changqing; Shen, Linghong; He, Ben
Abstract : Emerging evidence has revealed that all components of the renin-angiotensin system (RAS) are present in adipose tissue. Angiotensin II (Ang II), the major bioactive component of the RAS, has been recognized as an adipokine involved in regulating energy homeostasis. However, the precise role of Ang II in white adipose tissue (WAT) remodeling remains to be elucidated. In this present study, C57BL/C male mice were continuously infused with different doses of Ang II (1.44 mg/kg/d or 2.5 mg/kg/d) or saline for 2 weeks and treated with or without the Ang II type 1 receptor blocker valsartan. H&E staining and immunohistochemistry were conducted to investigate the white-to-brown fat conversion. The level of serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) was measured. RNA sequencing was employed to explore the differentially expressed genes and their enriched pathways between control and Ang II groups. Our results showed that Ang II substantially resulted in loss of body weight and fat mass. Most importantly, Ang II treatment induced WAT browning in mice, which was partially attenuated by valsartan treatment. Furthermore, Ang II perturbed the serum lipid profiles. Ang II treatment elevated serum levels of TC, TG, LDL-C, and HDL-C in mice. Mechanistically, thermogenesis, cell respiration, and lipid metabolism-associated mRNAs showed significantly increased expression profiling in Ang II-treated WATs compared with control WATs. Moreover, we found that Ang II treatment enhanced AMPK phosphorylation in adipocytes. Therefore, Ang II promotes WAT browning and lipolysis via activating the AMPK signaling pathway.